Studies on melatonin intervention in reactive oxygen species-linked autophagy of neocarzinostatin-induced varicocele infertility in male Swiss Albino mice - Olajumoke Omolara Ojo; Opeyemi Godwin Owajoba; Adebola Busola Ojo; Oluwafemi Adeleke Ojo (Elsevier, 2024)
Background: Varicocele is known to be a condition involving the impairment of spermatogenesis, thereby leading to low sperm production and decreased sperm quality and ultimately one of the major cause of male infertility. Melatonin has shown to directly neutralize a number of free radicals responsible for toxicity in the cell. Purpose: Therefore, this, study is designed to evaluate the induction of varicocele following neocarzinostatin treatment and also to investigate possible ameliorative effect of melatonin against varicocele induction. Method: In this study, male albino mice (aged 6 weeks and weighing 25 gs) were divided into eight groups (n = 10). Group I (Control), Group II -Varicocele (Positive Control), Group III -NCS (5 mg/kg.bwt), Group IV -NCS (10 mg/kg.bwt), Group V - NCS (20 mg/kg.bwt), Group VI- Varicocele + Melatonin (10 mg/kg.bwt), Group VII -NCS (10 mg/kg.bwt) + Melatonin (10 mg/kg.bwt), Group VIII -NCS (20 mg/kg.bwt) + Melatonin (10 mg/kg.bwt). Intraperitoneal injection of a mixture of ketamine and xylazine was administered into each mouse in group II and served as the positive control. Group III, IV and V received 5, 10 and 20 mg/kg.bwt of Neocarzinostatin daily respectively. Five mice from each group was sacrificed 24 hour (h) after the twenty-eight days treatment for further experiments while the remaining animals were used for fertility study. Results: At the end of the experiment, NCS treatment for 28 days reduced the body weight significantly decreased across the groups in a dose dependent manner (group II, III, IV, VI, VII and VIII). Swollen of the testis and enlarge blood vein were observed confirming the induction of varicocele by NCS-treated groups. Tubular Differential index (%) and Johnsen score (%) significantly reduced (p < 0.001) (p < 0.05). The levels of reactive oxygen species and malondialdehyde significantly increased (p < 0.001) (p < 0.05). The activities of glutathione, superoxide dismutase and catalase significantly reduced (p < 0.001) (p < 0.05). The level of Luteinizing Hormone, FSH and testosterone significantly reduced (p < 0.001) (p < 0.05). Conclusion: In conclusion, the results of this present study clearly showed that neocarzinostatin treatment leads to induction of varicocele infertility. Also, this study gives an insight that co-treatment of melatonin is able to reduce the hazardous effect of neocarzinostatin-induced varicocele and cytotoxicity in the testis of mice.